The interaction properties of costimulatory molecules revisited. - Collins, A; Brodie, D; Gilbert, R; Iaboni, A; Manso-Sancho, R; Walse, B; Stuart, D; Van Der Merwe, P; Davis, S (2002)
B7-1 and B7-2 are generally thought to have comparable structures and affinities for their receptors, CD28 and CTLA-4, each of which is assumed to be bivalent. We show instead (1) that B7-2 binds the two receptors more weakly than B7-1, (2) that, relative to its CTLA-4 binding affinity, B7-2 binds CD28 2- to 3-fold more effectively than B7-1, (3) that, unlike B7-1, B7-2 does not self-associate, and (4) that, in contrast to CTLA-4 homodimers, which are bivalent, CD28 homodimers are monovalent. Our results indicate that B7-1 markedly favors CTLA-4 over CD28 engagement, whereas B7-2 exhibits much less bias. We propose that the distinct structures and binding properties of B7-1 and B7-2 account for their overlapping but distinct effects on T cell responses.